O resgate da poética barroquizante haroldiana: o concretista (neo)barroco das Galáxias - Pellegrini, Renan Everton [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
This present work will aim to explore and come to the baroque resonances that pervade the poetics of Haroldo de Campos, from his incipient work linked to the voracity of concretist vanguard to Galáxias, explorative work of the boundaries between prose and poetry, impregnated with a baroque language; obviously resignified, rearranged and reallocated to contemporary needs, which may be called neo-baroque. It will be done the choice of some fragments, by way of pinching applicable characteristics to the Galáxias in general, considering the fact that, despite the fifty fragments that compose it, there is a certain independence and freedom of reading among them, much because the epiphanic character and the metaphor of the journey that permeate their origins, which, therefore doesn‟t preclude such an analytical method. The focus will be, a posteriori, in the analysis of some fragments of Galáxias, with the intent of come to the compositive techniques, treated on multireferences to authors and works that are estimated by him and in the experience of baroque‟s proliferation, which makes this book of essays be a spatiotemporal journey, made up of vertiginous epiphanies in which, pari passu, coexist and complement themselves playfulness and extreme ingenuity and craftsmanship signic

O presente trabalho terá como objetivo explorar e deflagrar as ressonâncias barrocas que perpassam a poética de Haroldo de Campos, partindo de sua incipiente obra vinculada à voracidade da vanguarda concretista às Galáxias, obra exploradora dos limites entre prosa e poesia, impregnada de uma linguagem barroca; obviamente ressignificada, rearranjada e realocada às necessidades da contemporaneidade, o que se convencionou denominar neobarroco. Far-se-á a escolha de alguns fragmentos, à guisa de pinçar características aplicáveis à obra Galáxias em geral, haja vista o fato de que, apesar dos cinquenta fragmentos que a compõem, há certa independência e liberdade de leitura entre eles, muito por conta do caráter epifânico e da metáfora da viagem que permeiam suas gêneses, o que, portanto, não inviabiliza tal método analítico. Deter-se-á, a posteriori, na análise de excertos de alguns dos fragmentos das Galáxias, com o intento de deflagrar as técnicas compositivas, calcadas nas multirreferências a autores e obras que lhe são caros e na experiência de proliferação barroca, o que faz desse livro de ensaios uma viagem espaciotemporal, composta de epifanias vertiginosas, nas quais, pari passu, convivem e complementam-se ludicidade e extrema engenhosidade ou artesania sígnica
Keywords: Campos, Haroldo de 1929-2003 Galáxias; Poetica; Poesia brasileira; Epifania; Brazilian poetry